Pre-treatment staging of multiple myeloma patients: comparison of whole-body diffusion weighted imaging with whole-body T1-weighted contrast-enhanced imaging. (June 2015) - Squillaci, Ettore; Bolacchi, Francesca; Altobelli, Simone; Franceschini, Luca; Bergamini, Alberto; Cantonetti, Maria; Simonetti, Giovanni
Background: Multiple myeloma (MM) is a hematologic malignancy characterized by the clonal proliferation of plasma cells. Accurate staging is of pivotal importance in the management of MM. Advanced imaging techniques, such as magnetic resonance imaging (MRI), are increasingly used for the initial diagnosis and staging of MM. Purpose: To compare whole-body (WB) MR diffusion-weighted imaging with background body signal suppression (DWIBS) with (WB) MR fat-suppressed T1-weighted contrast-enhanced imaging (T1-CE) in the pre-treatment staging evaluation of multiple myeloma (MM) patients. Material and Methods: Thirty-six patients with MM were included in the study. T1-CE and DWIBS were performed using a 3 T scanner. The Durie-Salmon plus staging system was used. Kappa statistics was used to assess agreement. Results: For all MM stages good to very good agreement was found for both T1-CE and DWIBS. The unweighted kappa statistic indicated a moderate, good and very good agreement between T1-CE and DWIBS for stages I, II, and III, respectively. In particular, in 67% of patients the MM staging according to T1-CE was not different from DWIBS. In the remaining 33% of patients, the MM stage obtained with T1-CE was lower than that provided by DWIBS. Conclusion: DWIBS and T1-CE were concordant in the majority of patients. In a minority of cases DWIBS evidenced areas of water restriction that did not correspond to contrast enhancement areas. Studies monitoring therapeutic response in relation to tumour burden and aggressiveness should be performed to assess the clinical relevance of DWIBS findings.